Understanding the role of aluminium in determining the surface structure and electrochemical performance of layered cathodes. Issue 27 (2nd July 2019) - Liu, Qi; Zhao, Yunhao; Liu, Weiwei; Wang, Meiyu; Ding, Jingjun; Feng, Yuzhang; You, Wenbin; Wang, Peng; Guan, Pengfei; Che, Renchao
Abstract : We elucidated the selective occupancy of Al ions and revealed the relationship between electrochemical performance and Al-ion behaviour. Abstract : The electrochemical properties of layered cathodes can be enhanced by doping with aluminium. However, understanding of the underlying mechanism of Al ion behaviour is deficient, which obstructs its further application. Herein, we adjusted the aluminium content in model LiNi0.85− x Co0.15 Al x O2 (LNCA) materials; the sample with the optimum aluminium content ( x = 0.05) exhibited excellent electrochemical performance (98.6% capacity retention at 275 mA g −1 ). Meanwhile, for the samples with excessive aluminium ( x = 0.15, 0.30), fast decay of the cycling stability could be observed. Meanwhile, their reversible capacities in the initial cycles were also greatly inferior to the theoretical values. These abnormal phenomena can be attributed to structure cracking and the impedance of Li-ion migration in samples with higher aluminium content. According to the microstructure observations, an unexpected beneficial heterostructure was found to cover the samples with optimum aluminium content, while in the samples with higher aluminium content, this heterostructure was not present. Furthermore, as confirmed by activation barrier calculations, Al ions were found to prefer to thermodynamically occupy the tetrahedral interstices instead of the octahedral sites in Li layers in a high delithiation state. Due to this selective occupancy, proper aluminium content can improve the stability of layered cathodes during cycling. However, excessive aluminium content instead impedes the formation of beneficial surface heterogeneity during synthesis and deeply affects Li-ion migration during cycling. Therefore, the electrochemical performance of the samples with higher aluminium content suffered severe decay. These results and discoveries significantly advance the guidance of microstructural design for next-generation layered cathode materials.